Virological and Serological Discordant Profiles in COVID-19 Pneumonia: Two Atypical Clinical Cases - Ranzenigo, Martina; Pastori, Claudia; Siracusano, Gabriel; Pariani, Elena; Uberti-Foppa, Caterina; Lopalco, Lucia (Frontiers in Immunology, 2020)
SARS-CoV-2 infection is primarily diagnosed through viral RNA positivity in nasopharyngeal swabs and it is associated to the early detection of specific immunoglobulins to SARS-CoV-2 proteins. We describe two moderate COVID-19 patients with WHO score 4/5 at the time of hospitalization, pneumonia and oxygen saturation <94% and with a strong discrepancy between viral-RNA and antibodies to SARS-CoV-2. One patient was positive for viral RNA but completely negative for binding and neutralizing antibodies, whereas the second patient was negative for viral RNA but with high level of both neutralizing and binding antibodies. This observation is relevant to understand the pathogenesis of this novel infection.